Analisis Yuridis Pemberian Hibah Dibawah Tangan Dikaitkan Dengan Pendaftarannya Pada Kantor Pertanahan Terhadap Penetapan Pengadilan Agama Medan Kelas I-A Nomor: 125/Pdt.P/2017/PA.Mdn - Kharisman Koima Batubara (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2020)
Grant is one of the transitions of property rights that have been regulated in the Code of Civil Law. The definition of a grant as explained in the provisions of Article 1666 of the Civil Code is something of an agreement with which the donor in his lifetime, free of charge and irrevocably, hand over an object for the purpose of the recipient of the grant who received the surrender. Grant is also one of worship that aims to strengthen the sense of affection between the donor and the recipient of the grant.This type of research is library research by discussing books, both primary and secondary books that explain the concepts of civil law and Islamic law.  Meanwhile, this research is comparative descriptive with normative approach. The research method used in this paper is normative-empirical legal research. The data used are secondary data and primary data derived from books, or legal literature, legislation, interviews and other materials that are included in the scope of the grant.Based on the results of the study, it can be obtained that the problem in this study is about the process of transitions the land rights cannot be carried out because the giving of the grant is done by means of a grant under the hand and the grantor has passed away before the transition process is done before a Notary.This is due to the lack of legal understanding of the procedure for land grants in accordance with the law and it has become their custom to comply with customary law which is allowed to do underhand grants without being done before a Notary and the grant is invalid if it is not done before a Notary except for those who are subject to customary law. Basically the grant is valid and consequently it applies to the parties if the receipt of the grant has received explicitly the gift (with a Notarial deed) this is regulated in article 1683, article 1682 of the Law Code. Based on the underhand grant of the donor who has died first before the transitions process of the rights in the legislation, a religious court decision is needed so that the transitions of land can be carried out. Keywords: Land, Underhand Grant, Notary